THE INFLUENCE OF LEADERSHIP AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT. PERMODALAN NASIONAL MADANI AT MEKAR UNIT IN PEKANBARU BRANCH - Dita, Irma; Pratikno, Yuni; Budiraharjo, Joko (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
With a simple random sampling technique, a sample of 75 employees was taken at PT. Permodalan Nasional Madani Mekaar Pekanbaru Branch as a respondent in this study. There is an Influence of Leadership on Employee Performance. It is proven that the t-value for the Leadership variable (X1) is 4.526 while the t-table value for n = 75 is 1.992. So 4.526> 1.992, then H0 is rejected and Ha is accepted, it can be stated that Leadership (X1) has a significant effect on Employee Performance (Y). There is an Influence of the Work Environment on Employee Performance. It is proven that the t-value for the Work Environment variable (X2) is 5.980, while the t-table value for n = 75 is 1.992. So 5.980> 1.992, then H0 is rejected and Ha is accepted, it can be concluded that partially the Work Environment variable (X2) has an effect on Employee Performance (Y). There is an influence of Leadership and Work Environment together on Employee Performance. It is proven that the ANOVA test obtained an F-value of 57.759, while the F-table (a 0.05) for n = 75 was 2.73. So Fcount > from Ftable (a 0.05) or 57.759 > 2.73 with a significant level of 0.000 because 0.000 < 0.05, then it can be said that Leadership (X1) and Work Environment (X2) together or simultaneously have a positive effect on Employee Performance (Y). The Adjudted R Square (R2) value is 0.605. This shows that 60.5% of Leadership (X1) and Work Environment (X2) together have an effect on Employee Performance (Y), while the remaining 39.5% is influenced by other factors not examined in this study.